MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA SISWA MADRASAH IBTIDAIYAH DENGAN METODE JOLLY PHONICS - Aisyah, Nur; Mayasari; Farida, Ida (Center of Language and Cultural Studies, 2021)
This study aims to examine the effectiveness of using the Jolly Phonics method to improve the students' initial reading ability at MI Raudhatus Shalihin. This research is an experimental research with a pretest-posttest one group sample design. The Jolly Phonics method is the independent variable and reading the beginning is the dependent variable. The next test is using Pre-Experimental Design Type One Group Pretest Posttest in a single group. The average posttest score was 67.69, while the average pretest score was 54.62. The results of hypothesis testing using the paired samples t test technique are known to have t count > t table or 3,930 > 2,179, so it can be concluded that there is a difference in the average learning outcomes between pre test and post test. Or in other words, using the Jolly Phonics method affects the initial reading results for first graders at MI Raudhatus Shalihin.